Communicating with Language Politeness in Arswendo Atmowiloto’s Cemara's Family 2 Novel - Nurhantoro, Tri Septa; Yohannes Angie Kristiawan; Yanus Purwansyah Sriyanto; Margaretha Resa Petria (JELLT (Journal of English Language and Language Teaching), 2024)
Politeness in communication is a crucial aspect in interactions. Politeness is shown in speech, attitudes, expressions, and so on which can describe one's personality and character. In verbal communication, politeness is shown in speech to the addressee, which needs to be considered in order to maintain a good relationship. The problem revealed in this research is how to implement language politeness in communication according to Leech (1983) shown in the dialogue in the novel Cemara's Family 2 by Arswendo Atmowiloto. The general aim of this research is to provide an overview of the implementation of language politeness for communication in the story of a family's life which can be a portrait of simple Indonesian society. This research uses pragmatic theory to analyze language politeness. The method used in this research is descriptive qualitative by digging from relevant literature and documents. Meanwhile, the technique used in analyzing the data is descriptive analysis technique by describing and interpreting the collected data so as to obtain an overview of language politeness. There are a total of 70 politeness data including: 18 data on tact maxim (25.7%), 7 data on generosity maxim (10%), 14 data on approbation maxim (20%), 6 data on modesty maxim (8.6%), 13 data on agreement maxim (18.6%), and 12 data on sympathy maxim (17.1%).